Characterization and sensorial evaluation of cereal bars with jackfruit - doi: 10.4025/actascitechnol.v33i1.6425 - Santos, Calila Teixeira; Bonomo, Renata Ferreira; Fontan, Rafael da Costa Ilhéu; Bonomo, Paulo; Veloso, Cristiane Martins; Fontan, Gabrielle Cardoso Reis (Acta Scientiarum. Technology, 2011)
The objective of this study was to elaborate a homemade and alternative cereal bar using dehydrated jackfruit and seed meal as fiber source, due to the availability of this fruit in the region, without reducing the nutritional values if comparing to those already existent in the market. In order to evaluate the centesimal content and the acceptance of the homemade bars, both light and traditional bars were used as reference. The results showed that the elaborated bar presented protein values very close with products already found in the market. However, the new bars presented higher content of fibers. Formulations of 30 and 40% of seed meal were the ones with the best acceptance.